Mechanisms of hypoglycemic action and pharmacokinetics - Ruban, E; Kolisnyk, T; Slipchenko, G (Annals of Mechnikov’s Institute, 2020)
Introduction. Diabetes mellitus is one of the most serious chronic diseases and considered to be non-infectious epidemic worldwide. Persistent hyperglycemia is a major hallmark of diabetes and risk factor for the development of its complications. Therefore, the main therapeutic goal in the treatment of diabetes is to reduce the elevated blood glucose level. Unfortunately, management of diabetes without any side effects is still a challenge to the modern medicine and pharmacy. Among potential alternatives to synthetic antidiabetic drugs plant polyphenols are very promising. However, polyphenol efficiency in diabetes is determined by their chemical structure and hence the affinity to a certain molecular targets in body tissues. Moreover, the bioavailability and other pharmacokinetic parameters of different individual substances may also vary significantly. In this context the present paper is devoted to the analysis of the available data on the hypoglycemic mechanisms and pharmacokinetics of various individual polyphenolic compounds in order to provide the necessary biopharmaceutical requirements in the development of a new blood glucose-lowering drug. Materials and methods. A systematic literature search of Pubmed, EMBASE and other databases with no language restrictionswas performed until to the end of August 2015. The following terms were used: polyphenols, diabetes mellitus, hypoglycemic action, pharmacokinetics and bioavailability of polyphenols. Results and discussion. According to available experimental data various polyphenols may influence carbohydrate metabolism at many levels. The mechanisms by which plant polyphenols exert their hypoglycemic action are mediated primarily by their ability to directly bind to target proteins (or peptides) and include inhibition of carbohydrate digestion and glucose absorption in the intestine, stimulation of insulin secretion from the pancreatic β-cells, modulation of glucose release from the liver, activation of insulin receptors and glucose uptake in the insulin-sensitive tissues. On the other hand, most polyphenols are characterized by low bioavailability mostly due to intensive metabolism. Thus absorption of such polyphenols as anthocyanins, phenolcarboxylic acids and some others appears low, but it is supposed that it could have been underestimated because not all metabolites might have been considered. Besides the absorption rate of these compounds is very rapid and may take place already in stomach. In contrary, rutin and other quercetin glycosides are absorbed only after release of the aglycones by the intestinal microflora. The elimination half-lives of most polyphenols tend to be short, especially in the case of anthocyanins. However, some polyphenolic compounds such as quercetin glycosides may have longer half-lives, and even accumulate in plasma with repeated ingestion. Conclusions. Polyphenols have unique therapeutic potential in the treatment of diabetes mellitus. Nevertheless, the possibility to use polyphenols as hypoglycemic agents in clinical practice is limited by their low bioavailability. Taking into account information reported in the literature on the hypoglycemic mechanisms and pharmacokinetics of polyphenols, promising method of increasing their bioavailability is the development of prolonged-release dosage forms based on polyphenol substances. This approach would extend residence time of polyphenols in the small intestine – the main site of hypoglycemic action in their intact, non-metabolized form, and will help maintain a constant concentration of active substances in the blood plasma, the target organs and tissues.